If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8m + -2m + -6 = 3m + 2m Reorder the terms: -6 + 8m + -2m = 3m + 2m Combine like terms: 8m + -2m = 6m -6 + 6m = 3m + 2m Combine like terms: 3m + 2m = 5m -6 + 6m = 5m Solving -6 + 6m = 5m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-5m' to each side of the equation. -6 + 6m + -5m = 5m + -5m Combine like terms: 6m + -5m = 1m -6 + 1m = 5m + -5m Combine like terms: 5m + -5m = 0 -6 + 1m = 0 Add '6' to each side of the equation. -6 + 6 + 1m = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 1m = 0 + 6 1m = 0 + 6 Combine like terms: 0 + 6 = 6 1m = 6 Divide each side by '1'. m = 6 Simplifying m = 6
| X/3=x/4-13 | | 2x-1x=10x | | 4(n+2)=8 | | 4x-6y=22 | | (4w+3)(1+w)=0 | | R=5g+5uforg | | 2x=11+6y | | 13x-27=3x-177 | | 4(7x+3)=54 | | x^2+9x+182=0 | | 48-4x=5x+22 | | 460=110+(x*8) | | 4x-115(x+2)-x= | | 2xln(5x)+x=0 | | -111-7x=8x | | 2x+(1-2x)=10x | | 8x-26=2(x-7) | | X=-10+3y | | 4(-4)-9=7(-4)+3 | | x+(3x-6)=90 | | 2x/3-4 | | (3+b)2=22 | | 7(2p-3)-8=6p+29 | | 4(z+5)-24=5z-3 | | 3x+18y=39 | | (x+10)=59 | | (3x/8)-(7x/16) | | 4(2)-9=7(2)+3 | | 6x+5=13x-75 | | x=3(10-x)/4 | | 3x/8-7x/16 | | 74+x=90 |